Shift rotation, overtime, age, and anxiety as predictors of offshore sleep patterns - Parkes, KR (American Psychological Association, 2014)
Shift work on offshore oil/gas installations necessitates 12 h shifts and rapid day/night shift changes. In the North Sea, both ‘fixed-shift’ (alternate day-shift and night-shift tours) and ‘swing-shift’ rotations (with a midtour shift change) are operated. The present study used survey data (n = 775) to examine sleep patterns over 3 ‘phases’ of the offshore work cycle (day shifts, DS; night shifts, NS; and leave weeks, LS) in relation to shift roster, overtime, age, offshore shift work exposure, and anxiety. Specific predictions were tested in a mixed-model ANOVA in which DS, NS, and LS sleep were treated as repeated measures. Sleep duration and sleep quality were predicted by significant interactions of phase with roster, anxiety, age, and shift work exposure, but the patterns of findings differed across DS, NS and LS. Consistent with other published findings, personnel working 2-week nights-to-days swing shifts reported shorter DS and NS sleep duration than those working fixed shifts. Extended 3-week tours (7 nights/14 days) showed an advantage only for DS sleep. There was no evidence that LS sleep was impaired following night-shift work. Overtime was negatively related only to NS sleep duration. Anxiety predicted poor NS and DS sleep; the relationship between age and NS sleep quality was curvilinear with minimum values at 38–42 y. Shift work exposure negatively predicted NS (but not DS or LS) sleep. The results are discussed in relation to the initial predictions; more general implications of the findings, and methodological limitations of the work, are considered in a final section.